ANALISIS YURIDIS PENGALIHAN OBJEK HAK TANGGUNGAN YANG SEDANG DIDAFTARKAN HAK ATAS TANAHNYA PADA KANTOR PERTANAHAN KOTA PEKANBARU - MELLIANA SUSANTY GINTING (PREMISE LAW JURNAL, 2016)
Every object of Collateral Right must be registered and have the right ti land certificate. Yet, for the lost of land that have not had cetificate can also be imposed with the Collateral Right if the provision of the Collateral Right is simultaneously done with the application for the registration of the relevant right to land.the data for this normative juridical study werw obtained trought documentation study an interview.that in the prosess of transferring the object of Collateral Right whose right to land is being registered must refer to the major agreement of both parties.the constraints faced in the process og transferring the riht to land whose Collateral Right is being registered are if the process of registrating the right to land registration is not yet accomplished due to something, but the binding of its Collateral Right still uses the power of attoney imposing Collateral Right (SKMHT), creditor as the preference creditor wants to transfer his/her object of Collateral Right, that it becomes a contraint in the transferring process because the registration process of the object of Collateral Right is not yet accomplished. Keywords:Transfer, Preference Creditor,Collateral Right